Testis biopsy in absolute head teratospermia: Is it a logical option?. Issue 2 (May 2020) - Shakhssalim, Nasser; Sadeghi, Mohamad Reza; Akhondi, Mohammad Mehdi; Akhavizadegan, Hamed
Introduction: Absolute head teratospermia (100% abnormal head morphology) is associated with poor fertility and assisted reproductive techniques results. We aimed to find if it is possible to bypass this disorder using sperm retrieved by testis biopsy. Methods: Multiple testis biopsies were performed in patients with infertility and absolute head teratospermia who were not able to provide semen on the injection day from 2006 to 2018. Then, the found sperms were evaluated based on being proper or not proper for intracytoplasmic sperm injection. Results: Only 2 patients, of a total of 22 (9%), had relatively proper sperms for microinjection. Discussion: There is no benefit to performing testis biopsy in non-azoospermic patients with absolute abnormal head morphology.